2005
DOI: 10.1089/ast.2005.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Spacecraft Components Affect the Aggregation of Microorganisms and May Lead to Different Survival Rates of Bacteria on Mars Landers

Abstract: Layers of dormant endospores of Bacillus subtilis HA101 were applied to eight different spacecraft materials and exposed to martian conditions of low pressure (8.5 mbar), low temperature (؊10°C), and high CO 2 gas composition and irradiated with a Mars-normal ultraviolet (UV-visible-near-infrared spectrum. Bacterial layers were exposed to either 1 min or 1 h of Mars-normal UV irradiation, which simulated clear-sky conditions on equatorial Mars (0.1 tau). When exposed to 1 min of Mars UV irradiation, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
6
33
0
Order By: Relevance
“…The current study provides evidence that Escherichia coli, a potential spacecraft contaminant (44,53), may survive but not grow on the surface of Mars. Results suggest that desiccation, UV irradiation, high salinity, and low pressure (in decreasing order of importance) were factors in reducing the number of viable E. coli cells over the course of the 7-day Mars simulations, consistent with related studies on microbial survival under Mars conditions (37,39,47,49,51,52).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current study provides evidence that Escherichia coli, a potential spacecraft contaminant (44,53), may survive but not grow on the surface of Mars. Results suggest that desiccation, UV irradiation, high salinity, and low pressure (in decreasing order of importance) were factors in reducing the number of viable E. coli cells over the course of the 7-day Mars simulations, consistent with related studies on microbial survival under Mars conditions (37,39,47,49,51,52).…”
Section: Discussionsupporting
confidence: 85%
“…Dispersal mechanisms of viable microbes away from landed or crashed spacecraft on Mars have not been adequately studied and remain significant black boxes in any Mars microbial survival and proliferation model. Long-term survival on Mars is unlikely if microbes are directly exposed to solar UV irradiation (11,37,47,49,50) but likely if the microbes are protected from UV irradiation by thin dust layers or embedded within UV-protected niches in spacecraft (33,39,47). In contrast, the greatest unknown in any Mars microbial survival and proliferation model is whether terrestrial microorganisms found on spacecraft are capable of growth and replication under Mars conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Vectran fabric types A and B proved to be even more problematic for recovery of spores, with only 5.9% and 8.8% recovery efficiencies. Differences in surface textural and physiochemical adhesive properties may be the reason for significant variations in the recovery efficiencies of the different surfaces (35) and, in particular, of Vectran fabric types. On the other hand, a recent publication demonstrated that different seeding methods for spores (dry or liquid deposition) can significantly affect sam-pling success (13).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, Mars environmental simulation experiments have been conducted to estimate (i) the survival rates of terrestrial microorganisms and (ii) the persistence of organic molecules on Mars (3,4,10,15,25,29,30,37,38,45). Historically, several studies have explored the resistance of bacterial spores to simulated Martian conditions (8,10,12,14, and references therein); these studies have concentrated mainly on the survival of spores of wild-type strains of various spore-forming species (10,32,(38)(39)(40). More recent experiments have attempted to better understand the molecular factors causing spore resistance to environmental extremes, in which mainly spores of the model organism Bacillus subtilis that carry mutations affecting spore protective factors or spore DNA repair systems have been used (9, 18-23; reviewed in references 16, 28, 41, and 42).…”
mentioning
confidence: 99%
“…Triplicate air-dried spore samples with a thickness of approximately 25 spore layers (for the 5 ϫ 10 8 spore concentration) on presterilized spacecraftqualified, chemfilm-treated aluminum 6061 coupons (13 mm in diameter by 1 mm thick) (23) were exposed to simulated Martian conditions in a cylindrical Mars simulation chamber (MSC) as described in detail previously (37). The simulated Mars environmental conditions listed in Table 2 (38)(39)(40). Spore recovery from coupons was accomplished by stripping off spores with polyvinyl alcohol, and viability assays were performed as described previously (18,19,21,22).…”
mentioning
confidence: 99%